Objective Structured Practical Examination as a tool of assessing practical skills in Clinical Physiology: perceptions of medical students and faculty: Perception of OSPE - Sharma, Anshul; Tahilramani, Hemant; Misra, Minakshi; Somani, Sheshav; Tak, Amit (Scripta Medica, 2022)
Background / Aim: Competence can be acquired in medical education if the assessment of students is multidimensional. Traditional practical assessments focus on testing the cognitive domain and compromise practical skills evaluation. The Objective Structured Practical Examination (OSPE) assesses skill-based competencies. The present study evaluates the feasibility and acceptability of OSPE through the perception of students and mentors. Methods: In this cross-sectional study, 100 medical students and 15 medical faculties enrolled from Pandit Deendayal Upadhyaya medical college, Churu (Rajasthan, India). The study included OSPE stations, conducted three OSPE sessions and obtained post-session feedback through a questionnaire, answered on 5 points Likert scale. The researchers calculated the response on various aspects of OSPE with percentages. Results: Students showed 94.4 % agreement for OSPE as a good learning experience and 93.5 % were satisfied with the content of OSPE. Students’ perception of OSPE as a reliable and fair tool for examination and administration was 94.66 % and 56.40 %, respectively. Although, 69.5 % of students agreed upon OSPE as a valuable tool compared with the traditional reviews. The overall agreement of faculty for the competence of OSPE was 75.74 %. Conclusion: The acceptance of OSPE by medical students and faculty may lead to the introduction of this tool in assessing practical skills in medical teaching and helping students better acquire knowledge and skills and assisting faculty in teaching modifications, as per the needs of students. So, OSPE supplements the traditional methods in clinical physiology practical assessments.